Pengaruh Brand Image, Brand Awareness Dan Viral Marketing Terhadap Keputusan Pembelian Pada Produk Somethinc (Studi Kasus Pada Mahasiswa di Kota Malang) - Nur Rohmah, Febyana Jihan; Nurhidayah, Nurhidayah; Wahyuningtyas, Nanik (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to examine how brand image, brand awareness, and viral marketing impact the purchasing choices of specific products among students residing in Malang. Utilizing the multiple linear regression technique, the research concentrates on explanatory investigation employing a quantitative approach. A sample of 85 participants was selected using the Malhotra formula. Data analysis was conducted through SPSS version 25 software, encompassing validity, reliability, normality, classical assumption, hypothesis, and determination coefficient (R2) tests. The findings reveal that collectively, brand image, brand awareness, and viral marketing significantly influence consumer purchasing decisions for Somethinc products among students in Malang City. Keywords: Brand Image, Brand Awareness, Viral Marketing, Purchace Decisions